The Effects of Work-Family Conflict, Self-Efficacy, and Workload on Employee Performance at PT. BPR Artha Bali Jaya (Head Office) - Anggi Septiani; I Gede Rihayana; I Komang Oka Permadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to analyze the influence of work-family conflict, self-efficacy, and workload on employee performance at PT. BPR Artha Bali Jaya (Head Office). This is a quantitative study. The population in this study consists of all employees of PT. BPR Artha Bali Jaya (Head Office), totaling 40 people. The sampling technique used is the Saturated Sampling Technique, where the selection in this study utilizes the entire total population. The data analysis technique used in this study is Multiple Linear Regression Analysis. The results of the study indicate that work-family conflict has a negative and significant effect on employee performance at PT. BPR Artha Bali Jaya (Head Office). Self-efficacy has a positive and significant effect on employee performance at PT. BPR Artha Bali Jaya (Head Office). Workload has a negative and significant effect on employee performance at PT. BPR Artha Bali Jaya (Head Office).